Emotion regulation choice in female patients with borderline personality disorder: Findings from self-reports and experimental measures. (30th August 2016) - Sauer, Christina; Sheppes, Gal; Lackner, Helmut Karl; Arens, Elisabeth A.; Tarrasch, Ricardo; Barnow, Sven
Abstract: Emotion dysregulation is a core feature of borderline personality disorder (BPD). So far, many studies have tested the consequences of the implementation of certain emotion regulation (ER) strategies, but there have been no investigations about ER choices in BPD. Thus, the aim of this study was to investigate habitual ER choices by self-report questionnaires and experimentally by testing the preference to select between distraction and reappraisal when facing different emotional intensities (high vs. low) and contents (borderline-specific vs. unspecific negative) in patients with BPD ( n =24) compared with clinical controls (patients with major depression, n =19) and a healthy control group ( n =32). Additionally, heart rate (HR) responses were continuously assessed. Main results revealed that both patient groups showed maladaptive self-reported ER choice profiles compared with HC. We found, however, no differences between the groups in the choice of distraction and reappraisal on the behavioral level and in HR responses. In BPD, within-group analyses revealed a positive correlation between symptom severity and the preference for distraction under high-intensity borderline-specific stimuli. Our findings provide preliminary evidence of ER choices in BPD and show the robustness of the choice effect in patients with affective disorders. Highlights: Patients with BPD showed maladaptive ER choice profiles in self-report measures. Patients with BPD showed the same ER choice behavior like HC in experimental measures. Findings underline the importance of training cognitive ER strategies in patients with BPD.